GST and its implication: Detailed perspective - Dr. Mahender Kumar (International journal of economic perspectives, 2021)
Goods and service tax which is considered as one of the pioneer financial reforms after independence was first presented in the parliamentary session of 2005-2006 by the Vajpayee led government. Experts and analysts from Empowering committee headed by Asim das gupta brought forwarded strategies for its implementation and for studying its implications but due to lots of complications GST missed its deadline of rolling out in the year 2010.In 2011 the constitutional amendment bill was again brought into consideration but again due to lack of government coordination and the majority issues it couldn’t be implemented.